Permian-Jurassic Palaeogeography of the SE Banda Arc Region - Charlton, Tim (Ikatan Ahli Geologi Indonesia, 2012)
Palaeogeographic maps covering the southern and eastern sectors of the Banda forearc (Savu to the Kei islands, also including Timor and the Tanimbar islands) and adjacent parts of the northwest Australian continental margin are presented for the Early Permian, Middle-Late Permian, Early-Middle Triassic, Late Triassic, and Early, Middle and Late Jurassic. A series of palaeotectonic reconstructions from the Devonian to the mid-Tertiary show an interpretation of the sequential phases of rifting that dismembered northeastern Gondwanaland through this period. Three major phases of rifting are documented for the core region of the future Banda forearc, commencing in the Early Permian, Late Triassic and Middle/Late Jurassic. Each rift event is characterised palaeogeographically by high facies diversity, which is a consequence of strong differential vertical crustal movements at that time. The three rift phases are separated by two quieter tectonic intervals characterised palaeogeographically by low facies diversity (widespread development of marine shales) during phases of post-rift thermal subsidence.